The Kelayakan Finansial Dan Strategi Pengembangan Pabrik Mini Coklat (Kasus PT Perseroda PT. Aneka Usaha Laba Jaya Utama, Lampung) Financial Feasibility And Development Strategy Mini Chocolate Factory (Case Of Pt Perseroda Pt. Aneka Usaha Laba Jaya Utama, : (Kasus PT Perseroda PT. Aneka Usaha Laba Jaya Utama, Lampung) - Wan Abbas Zakaria; Lidya Sari Mas Indah; Otik Nawansih; Fibra Nurainy; Amanda Putra Seta (Jurnal Penelitian Pertanian Terapan, 2023)
The mini factory operated by PT Aneka Laba Jaya Utama (AULAJU) is the only mini factory in Lampung Province.  However, the current business activities seem to be "running in place" and even chocolate production has stopped for almost a year.  Therefore, a financial feasibility study was carried out as a basis for planning for the development of PT AULAJU's chocolate production business.  The research was conducted at the Perseroda PT AULJU, Pesawaran Regency, Lampung Province.  The analysis used in this study is testing the investment criteria, that are Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), Gross Benefit Cost Ratio (Gross B/C), dan payback period (PP).  The business development strategy was analyzed using SWOT analysis.  The results of the discussion show that PT. AULAJU was declared eligible to be run and developed because NPV=27 billion >0 (positive), IRR=86%>BRI Bank interest rate 12%, Net B/C=1,01>1, Gross B/C=2,01>1, and PP=1,44 (Payback Period< maximum time/economic life of investment (10 years).  On the other side, PT AULAJU must make improvements in the context of developing its business. The three main priority strategies are 1) Repair and rejuvenation of machinery and factory equipment that have been damaged or are no longer used, 2) Optimizing the management of BPOM and Halal production permits, etc., 3) Improving the management of BUMD management.